DINOCHLOA MALAYANA S.DRANSF. (POACEAE: BAMBUSOIDEAE), A NEW RECORD FOR INDONESIA - I Putu Gede Parlida Damayanto (Reinwardtia, 2018)
DAMAYANTO, I P. G. P. 2018. Dinochloa malayana S.Dransf. (Poaceae: Bambusoideae), a new record for Indonesia. Reinwardtia 17(1): 35-37. - Dinochloa malayana was previously only known from Peninsular Malaysia and Southern Thailand. However, recently, this bamboo was also found at Karimun Anak Island and Batam Island,Indonesia. A description, notes and photographs of this species are presented. An identification key to Sumatran Dinochloa is also provided.